2021
DOI: 10.1093/ajcn/nqab274
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid removal during hemodialysis can be compensated for by protein ingestion and is not compromised by intradialytic exercise: a randomized controlled crossover trial

Abstract: Background Patients with end-stage renal disease (ESRD) undergoing hemodialysis experience a rapid decline in skeletal muscle mass and strength. Hemodialysis removes amino acids (AAs) from the circulation, thereby lowering plasma AA concentrations and stimulating proteolysis. Objectives In the present study, we evaluate the impact of intradialytic protein ingestion at rest and following exercise on AA removal and plasma AA av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Therefore, the supply of intradialytic meals may be a therapeutic opportunity to improve PEW and health-related quality of life, particularly in malnourished patients, unless there is a low risk of postprandial hypotension, digestive symptoms, or aspiration. Recently, it was reported that the intake of milk protein (40 g) 1 h after the start of dialysis compensates for amino acid loss from the dialysate effluent and maintains plasma amino acid concentrations until the end of the dialysis session [ 70 ].…”
Section: Nutritional Supplementation For Pewmentioning
confidence: 99%
“…Therefore, the supply of intradialytic meals may be a therapeutic opportunity to improve PEW and health-related quality of life, particularly in malnourished patients, unless there is a low risk of postprandial hypotension, digestive symptoms, or aspiration. Recently, it was reported that the intake of milk protein (40 g) 1 h after the start of dialysis compensates for amino acid loss from the dialysate effluent and maintains plasma amino acid concentrations until the end of the dialysis session [ 70 ].…”
Section: Nutritional Supplementation For Pewmentioning
confidence: 99%
“…This also may work synergistically with exercise interventions, although more research is needed. A recent study showed that protein ingestion (40 g dose of milk protein concentrate) during HD sessions compensated for the reductions in AA during dialysis (AA removal) [37 ▪▪ ]. They also additionally performed exercise sessions (dialysis cycle ergometer) and showed that exercise did not have a negative effect on reducing plasma AA.…”
Section: Treatmentsmentioning
confidence: 99%
“…BCAAs can improve muscle structure and function in patients with sarcopenia [64]. Because many BCAAs are lost during dialysis, previous studies have reported that blood BCAA levels are maintained in patients on dialysis using dialysate containing physiological concentrations of BCAAs or consuming protein before dialysis [65,66].…”
Section: Nutritional Managementmentioning
confidence: 99%